Determination of fluid dynamic bearing (FDB) oil and pivot grease in hard disk drive components via gas chromatography-mass spectrometry / Goh Yin Shean - Goh, Yin Shean (2014)

(untitled)
Fluid dynamic bearing (FDB) oil and pivot grease are used as lubricant in the spindle motor and in the actuator pivot bearing cartridge in the hard disk drive (HDD). The presence of high amount of both FDB oil and pivot grease in hard disk drive may lead to the drive failure. Determination of FDB oil and pivot grease presence in the HDD after 300 hours, 600 hours and 900 hours of testing in reliability chamber was done by extracting the recirculation filter and adsorbent breather filter in the HDD using hexane as the solvent. The presence of FDB oil and pivot grease in the extracted solvent from the recirculation filter and adsorbent breather filter was determined via gas chromatography (GC) and identified by mass spectrometry (MS). The amount for both FDB oil and pivot grease were found to increase with the HDD test time. At the point of saturation, the internal HDD environment contains 116 ng/sample of FDB oil and 1120 ng/sample of pivot grease based on the recirculation filter extraction. However, this amount of vapors were able to be removed by the adsorbent breather filter as it has yet to reach the maximum amount that it can absorb.